Monitoring the agri-food system in Myanmar: Mechanization service providers – June 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Mechanization service providers (MSPs) in Myanmar were originally interviewed by phone in the summer and fall of 2020. The phone surveys covered combine harvester SPs (CHSPs) and tractor SPs (TSPs) to determine how their businesses were affected by COVID-19 related restrictions. The results of those surveys were published in Myanmar Strategy Support Program Notes 07, 12, 17, 39, and 43, respectively. To trace the continuing impact of the COVID-19 pandemic and the current political and social conditions on their economic activities, a sixth phone survey of MSPs was conducted in early June 2021. This Research reports on the results of the sixth survey as well as on trends from earlier surveys.